Statistical analysis of midlatitude spread F using multi-station digisonde observations. (January 2018) - Bhaneja, P.; Earle, G.D.; Bullett, T.W.
Abstract: A comprehensive statistical study of midlatitude spread F (MSF) is presented for five midlatitude stations in the North American sector. These stations include Ramey AFB, Puerto Rico (18.5°N, 67.1°W, −14° declination angle), Wallops Island, Virginia (37.95°N, 75.5°W, −11° declination angle), Dyess, Texas (32.4°N, 99.8°W, 6.9° declination angle), Boulder, Colorado (40°N, 105.3°W, 10° declination angle), and Vandenberg AFB, California (34.8°N, 120.5°W, 13° declination angle). Pattern recognition algorithms are used to determine the presence of both range and frequency spread F. Data from 1996 to 2011 are analyzed, covering all of Solar Cycle 23 and the beginning of Solar Cycle 24. Variations with respect to season and solar activity are presented, including the effects of the extended minimum between cycles 23 and 24. Highlights: Statistical study gives solar and seasonal cycle variation of MSF using digisonde data from 5 stations in North-America. There are more and longer events during solar minimum years for all 5 stations. Seasonal variation shows longitudinal variation of MSF and each station has maximum MSF occurrence for different seasons The longitudinal variation is due to TIDs, electrodynamical or geomagnetic coupling, tropospheric forcing or orography.